Food habits of snakehead, Channa striatus (Bloch), in the lotic streams of Universiti Putra Malaysia, Malaysia - Sarker, Mohammad Nurul Amin; Ara, Roushon; Mohammad, Hafiz; Arshad, Aziz (WFL Publisher, 2014)
Stomach contents were used to investigate the food and feeding habits of Channa striatus, collected from the lotic streams in Ladang 10, Universiti Putra Malaysia, Malaysia. Samples were collected twice a month between September and November 2012. In total, 120 stomachs of C. striatus both adults and fry were examined. Analysis of preys in stomach showed 7 major food items for both adults and fry of C. striatus. The most important diet of fry according to the simple resultant index (%Rs) was copepods (23.37%). This was followed by cladocerans (20.52%), insects (20.07%), molluscs (13.70%), worms (9.58%), shrimps (9.12%) and others (3.65%). Predominant diet found in the stomach of adult was aquatic insects (27.46%). This was followed by shrimps (22.51%), small fish (17.48%), others (15.55%), semi digested materials (11.25%), worms (3.31%) and part of fish (2.43%). The feeding intensity was very poor in adult fishes during the experimental period. The fry fed actively throughout the study period where most of them were found to be full stomach. It could be concluded that both fry and adult C. striatus are carnivorous.